Cambridge Rocketry Simulator – A Stochastic Six-Degrees-of-Freedom Rocket Flight Simulator. Issue 1 (21st February 2017) - Eerland, Willem J.; Box, Simon; Sóbester, András
The Cambridge Rocketry Simulator can be used to simulate the flight of unguided rockets for both design and operational applications. The software consists of three parts: The first part is a GUI that enables the user to design a rocket. The second part is a verified and peer-reviewed physics model that simulates the rocket flight. This includes a Monte Carlo wrapper to model the uncertainty in the rocket's dynamics and the atmospheric conditions. The third part generates visualizations of the resulting trajectories, including nominal performance and uncertainty analysis, e.g. a splash-down region with confidence bounds. The project is available on SourceForge, and is written in Java (GUI), C++ (simulation core), and Python (visualization). While all parts can be executed from the GUI, the three components share information via XML, accommodating modifications, and re-use of individual components.